57 The Impact of Functional Teat Number on Piglet Survival and Sow Efficiency. (7th May 2021) - Obermier, Dalton; Eickhoff, Megan; Mote, Benny E; Uitermarkt, Amanda; Frobose, Hyatt; Borg, Bart
Abstract: Pre-weaning mortalities have become a pressing issue in modern swine production. Litter size at birth has greatly increased through direct genetic selection. Unfortunately, little emphasis was placed on improving functional teat number, resulting in a nutrient access shortage. Therefore, a total of 750 sows consisting of three genetic lines in a commercial barn in Nebraska, USA, were used to evaluate the impact of functional teat number on piglet survival. Teat traits recorded at farrowing included total teat number (TT), functional teat number (FT), and non-functional teat number (NFT); with population means of 14.84 (1.21), 14.55 (1.30), and 0.28 (0.56), respectively. Production traits recorded included total number born (TNB), wean number (WN), total pre-weaning mortality (PWM), and post-cross foster mortality (CFPWM). The lm function within RStudio was used to estimate regressions, with parity and piglets placed (PP) used as covariates for WN and CFPWM, and parity, PP, and TNB for PWM. One additional FT increased WN (P < 0.01; 0.33), and reduced PWM (P < 0.01; -3.04%) and reduced CFPWM (P < 0.01; -3.71%). A subset of 274 sows were used to determine the effects of increasing functional teats on sow and piglet efficiency. Additional traits recorded included sow average daily feed intake (ADFI), backfat loss (BF) and average piglet weaning weight (WW). Parity, ADFI, backfat-entry, and WN were used as covariates for BF; parity, backfat-entry, and WN for ADFI; and parity, PP, ADFI, and WN were used for estimating WW. Regression estimates showed that an additional functional teat had no significant impact (P > 0.05) on ADFI, BF, or WW. Taken together, these results suggest that improving functional teat number does not impact ADFI or BF for sows and does not influence average piglet weaning weight, but it does decrease PWM resulting in more pigs weaned per litter.